Muscle versus Fasciocutaneous Flap in Lower Limb Reconstruction: Is There a Best Option? - Cherubino, Mario; Corno, Martina; D'Arpa, Salvatore; Di Summa, Pietro; Pellegatta, Igor; Valdatta, Luigi; Ronga, Mario (Journal of Reconstructive Microsurgery, 2017)
Soft tissue defects of the lower extremity that expose underlying bones, joints, and tendons pose challenging problems and generally require free tissue transfer for a successful reconstruction. Historically, muscle flaps were the gold standard choice for lower limb reconstruction. To obviate the unpredictable appearance and high donor-site morbidity of muscle flaps, fasciocutaneous flaps were introduced. Recently, perforator flaps, such as the anterolateral thigh flap, gained a leading role in the reconstructive scenario. There is growing evidence in the literature supporting that fasciocutaneous and perforator flaps are comparable to muscle flaps in terms of flap survival, postoperative infection, osteomyelitis, bone union, and ambulation. With the advances of knowledge in perforator anatomy and their mapping, a new era of lower limb reconstruction has begun. Propeller flap could be raised on any suitable perforator vessel and, without the aid of microsurgical anastomosis, used to restore small- to middle-sized soft tissue defects. In this review, we intend to analyze pros and cons of muscle and fasciocutaneous free flaps and the applicability of the propeller flaps in lower limb reconstruction.
Keywords: lower limb reconstruction; free flaps; muscle flaps; fasciocutaneous flaps